Specific Aspects of Linguistic Study of Literary Characters - Ullieva Sanobar Khaydarovna (Zien Journals, 2023)
An essential condition for the successful mastery of Russian language is the assimilation of language norms and the development of skills and abilities of verbal communication. The formation of speech competence is one of the components of the formation of communicative competence - the main goal of teaching Russian language at university according to the State Educational Standard. The shift in emphasis from the study of language to the study of speech led to an increased interest in stylistics
Keywords: expression; intonation; rhythm; personality